Efficient Low-Temperature Nutrient Removal from Agricultural Digestate using Microalgae - Ievina Baiba; Romagnoli Francesco (Environmental and Climate Technologies)
In the face of energy crises and climate change, microalgae present a promising solution for sustainable energy production and carbon dioxide sequestration. Recently, digestate has been considered a cost-effective nutrient source for microalgae cultivation. Utilizing digestate not only enhances the sustainability and economic feasibility of microalgal biofuels but also offers a method for wastewater treatment. Nevertheless, the application of digestate is limited by its high optical density and a substantial amount of total solids. In the current study, several pretreatment methods were tested to increase the feasibility of digestate application for microalgae cultivation. Our findings show that various centrifugation methods and filtration decrease total solids’ content but are ineffective in reducing optical density. Although the use of microalgae in treating various wastewaters has shown promising outcomes, the effectiveness of nutrient removal at low temperatures remains largely unexplored. To fill this gap, green microalga Chlorella sorokiniana was cultivated in pretreated diluted liquid digestate in dynamic springtime weather at high-latitude conditions. An innovative pilot-scale open race-way pond system was integrated into a biogas plant using its side streams, namely liquid digestate and flue gases as nutrient and CO2 sources for microalgae cultivation. Coupling biogas production with microalgae cultivation can provide various benefits, including nutrient recycling from liquid digestate and CO2 sequestration from flue gas. During the cultivation, high solar irradiance and low temperatures were recorded resulting in suboptimal conditions for C. sorokiniana growth. Despite the low productivity of C. sorokiniana, its nutrient removal efficiency was notably high. C. sorokiniana effectively removed 83 % of nitrogen and 85 % of phosphorus, demonstrating the promising potential of microalgae for wastewater treatment in high-latitude regions.